WAQF MANAGEMENT ACCORDING TO LAW NUMBER 41 OF 2004 ON WAQFIN: A case study at the Al Muslim University Foundation Indonesia - Muthawalli; Ida Friatna; Husni bin Abdul Jalil (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article aims to analyse the management of waqf by institutional trustees at the Almuslim University Foundation in Bireuen from the perspective of Law No. 41 of 2004 on Waqf and fiqh muamalah. This study employs a qualitative method with a legal-empirical approach to evaluate the alignment between normative regulations and the practice of managing productive endowments at the institutional level. The findings reveal that the Almuslim University Foundation in Bireuen has fulfilled its role as a nazir by endeavouring to develop endowment assets, such as constructing educational facilities and engaging in productive collaborations. However, this management still faces several challenges, including the lack of integrated financial reporting, the dominant use of endowment proceeds for consumptive financing without a long-term capitalization strategy, and the risk of legal uncertainty regarding the status of assets derived from management, which could trigger administrative disputes. These conditions pose a potential threat to the accountability and sustainability of the social and economic functions of endowments. Therefore, institutional capacity building, enhancing the professionalism of administrators, improving digital-based reporting systems, and optimising oversight by the Indonesian Waqf Board are necessary. These findings underscore that the implementation of professional and transparent waqf governance principles is key to making waqf a sustainable and accountable instrument for community empowerment.